Championing awareness of the opioid epidemic through a service-learning module for non-STEM biology majors - Fleming, Ryleigh; Adkins, Sarah J.; Esteban, Marco; Cross, Cinnamin; Chatham, Amy Hutson; Raut, Samiksha A. (Frontiers in Education, 2023)
Over 50,000 people die annually from opioid overdoses in the United States leading to what has become known as the “opioid epidemic.” This is of heightened concern in states like Alabama that experience higher rates of overall drug use and overdose deaths. Thus, it is increasingly important for college students in Alabama to learn about how the opioid epidemic is affecting their communities. Previous studies have demonstrated that engaging non-majors in innovative active-learning oriented pedagogies like service-learning can enhance their understanding and awareness about contemporary societal issues. Despite its pedagogical potential, the impact of opioid-related service-learning, particularly for non-majors, continues to remain unexplored. In this study, we describe the implementation of a service-learning module centered on opioid addiction. Students in a non-major biology course learned the science behind opioids, had Naloxone training, and engaged in active discussions with an opioid researcher, physician, and former illicit opioid user. Our assessment of the thematic analysis of pre- and post-reflection free-write data from 87 consenting students revealed 10 categories that students reported in the post- but not pre-reflections (essay gain), pre- and post-reflections (neutral), and pre- but not post-reflections (essay loss). We found essay gains in students humanizing addiction and awareness of the cultural context of opioid addiction and essay losses from students indicating that non-major students had a low level of awareness related to these issues. Eight one-on-one, semi-structured interviews revealed that students were personally impacted by the epidemic and valued its curricular inclusion. Our data supports that service-learning can increase non-major biology student’s awareness and contextual understanding about the opioid epidemic, enabling much-needed advocacy to further enhance its awareness among the public.